Digitising key workflows in the precast concrete supply chain : a BIM cloud-enabled system for productivity improvement - Phang, Thomas C. H. (Nanyang Technological University, 2021)
A typical construction project will entail many players at various stages and involves functions such as design, construction, and fabrication. It largely includes the client, designer, main contractor, and a precast concrete (PC) manufacturer’s involvement from the start to finish of the project. Earlier research has revealed that traditional construction practices caused many problems associated with fragmentation, predominantly due to the lack of communication and coordination between stakeholders. This has led to unnecessary delays and disputes among stakeholders during the construction stage. The problem is further worsened as the work flows downstream to sub-contractors such as PC manufacturers. Across the globe, the governments of developed countries have been implementing building information modelling (BIM) in the construction industry to transform the value chain to enhance the workflows in the construction industry. However, the literature on BIM focusing on the precast concrete segment is under-developed. And as off-site fabrication of building components is becoming progressively common, it becomes imperative to focus on PC manufacturers and identify areas of enhancement. This in turn will increase the overall productivity of the PC supply chain. This research takes the perspective of PC manufacturers. The study first establishes a baseline understanding of the status of BIM adoption among the PC manufacturers. As such, a BIM adoption model is created from the perspectives of PC manufacturers to explain the organisations’ BIM adoption status, and the PCBIM hexagon framework was proposed to identify the critical success factors (CSFs) that affect their BIM adoption status. A total of eight factors have been identified as the CSFs to BIM adoption. In addition, these CSFs were further assessed to determine factors that directly contribute to productivity improvement and the PC-CSF performance analytical model is developed. A total of four CSFs have been shortlisted: (1) BIM utilisation, (2) top management commitment, (3) team coordination and (4) information sharing. The author called these factors the “PC-CSF performance factors”. The results concluded that the CSFs for BIM adoption can certainly facilitate PC manufacturers towards higher levels of technology utilisation, however not all the CSFs directly contribution to the productivity improvement of the PC manufacturers. To demonstrate and validate the usefulness of the PC-CSF performance analytical model for real-world problem-solving, an established PC manufacturer was selected to conduct the case studies. Three key workflows in the PC supply chain were identified and the four PC-CSF performance factors were applied collectively. The field results have proven that the combined benefits of the PC-CSF performance factors can improve the productivity of the PC manufacturer and its supply chain.